Terrifying tales - Scieszka, Jon; Grimly, Gris; Gidwitz, Adam; Stine, R. L.; Pilkey, Dav, 1966-; Buckley, Michael, 1969-; Legrand, Claire, 1986-; Loftin, Nikki; Griffin, Adele; Barnhill, Kelly Regan; Older, Daniel José; Williams-Garcia, Rita (Guys read, 2015)
"Eleven masters of suspense have come together to bring you a bone-chilling collection of original ghost stories perfect for sharing around the campfire, reading under the covers with a flashlight, and scaring your friends' pants off"--Front jacket flap.